2013
DOI: 10.1002/dvdy.24028
|View full text |Cite
|
Sign up to set email alerts
|

Region‐specific epithelial cell dynamics during branching morphogenesis

Abstract: Background-Epithelial cells of developing embryonic organs, such as salivary glands, can display substantial motility during branching morphogenesis. Their dynamic movements and molecules involved in their migration are not fully characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 47 publications
3
24
0
Order By: Relevance
“…A gradient of speeds was observed, with the fastest cells located near the front (Spearman r=0.77 and P<0.0001). Similar regional differences in cell speed have been described in the mouse salivary gland, suggesting a conserved mechanism for epithelial tube elongation (Hsu et al, 2013). By contrast, despite variations within individual branches, persistence displayed no consistent correlation with distance from the front (Spearman r=−0.11 and a non-significant P-value) (Fig.…”
Section: Elongation Correlates With An Increase In Cell Motilitysupporting
confidence: 71%
See 2 more Smart Citations
“…A gradient of speeds was observed, with the fastest cells located near the front (Spearman r=0.77 and P<0.0001). Similar regional differences in cell speed have been described in the mouse salivary gland, suggesting a conserved mechanism for epithelial tube elongation (Hsu et al, 2013). By contrast, despite variations within individual branches, persistence displayed no consistent correlation with distance from the front (Spearman r=−0.11 and a non-significant P-value) (Fig.…”
Section: Elongation Correlates With An Increase In Cell Motilitysupporting
confidence: 71%
“…Consistent with this conceptual model, we identified a gradient of cell speeds running from slow in the body of the organoid to fast in the high-pERK tips of elongating ducts. High levels of cell motility in the elongation front have also been observed in the mouse salivary gland (Hsu et al, 2013). We next demonstrated that both cell migration and branch elongation require Rac1 and MAPK signaling.…”
Section: The Cell Behavioral Basis Of Tube Elongationmentioning
confidence: 53%
See 1 more Smart Citation
“…E-cadherin plays an important role in the development of the SMG, [51][52][53][54][55] in particular to provide survival signals to maturing duct cells. 55 Recent studies have shown that cells dispersed from salivary gland tissues in mice and humans can self-assemble to acinar-like structures in vitro and display characteristics of native gland structures.…”
Section: Figmentioning
confidence: 99%
“…PEG hydrogels are bioinert, 26 and they lack cell-matrix and cell-cell interactions that are commonly utilized to maintain survivability of sensitive cell types. 32,38,41,49,50 As cell-cell interactions, in particular, play a vital role in salivary gland cell functions in vitro and during gland development, 20,[51][52][53][54][55][56][57] we also explored the use of SMG cell aggregation into microspheres to increase longterm viability of hydrogel-encapsulated SMG cells. Finally, we examined the cellular composition and proliferative potential of the encapsulated SMG microspheres.…”
mentioning
confidence: 99%